2020
DOI: 10.1051/0004-6361/201937404
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic twist profile inside magnetic clouds derived with a superposed epoch analysis

Abstract: Context. Magnetic clouds (MCs) are large-scale interplanetary transient structures in the heliosphere that travel from the Sun into the interplanetary medium. The internal magnetic field lines inside the MCs are twisted, forming a flux rope (FR). This magnetic field structuring is determined by its initial solar configuration, by the processes involved during its eruption from the Sun, and by the dynamical evolution during its interaction with the ambient solar wind. Aims. One of the most important properties … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 49 publications
2
37
1
Order By: Relevance
“…(25) and (26). We note that all c B values reported in Lanabere et al (2020) are larger by a factor 2. This rescaling does not change any of their conclusions.…”
Section: Distribution Of the Magnetic Asymmetrymentioning
confidence: 62%
See 2 more Smart Citations
“…(25) and (26). We note that all c B values reported in Lanabere et al (2020) are larger by a factor 2. This rescaling does not change any of their conclusions.…”
Section: Distribution Of the Magnetic Asymmetrymentioning
confidence: 62%
“…The asymmetry of the magnetic field intensity in MCs was quantified by Janvier et al (2019) and Lanabere et al (2020). They used the coefficient c B,t , which is defined as…”
Section: Magnetic Asymmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…This technique has been used in a variety of cases, in particular in the SW for the investigation of corotating interaction regions (Yermolaev et al, 2015), ICMEs (Janvier et al, 2019), and MCs (Masías-Meza et al, 2016;Rodriguez et al, 2016). A recent study also investigated, using the SEA technique, the profile of the magnetic field twist within MCs (Lanabere et al, 2020). Masías-Meza et al (2016) analyzed how the generic profiles of MCs change depending on their propagation speed.…”
Section: 1029/2020ja028150mentioning
confidence: 99%
“…Wang et al (2018) and Zhao et al (2018), on the other hand, found that twist decreases monotonically from the axis to the periphery of FRs using a velocity-modified GH model (Wang et al 2016) that considers dynamic evolution of MCs. In contrast, Lanabere et al (2020) recently applied a superposed epoch analysis to MCs and analyzed their magnetic components in the FR frame, finding that the typical twist distribution of MCs is nearly uniform across the central region and increases moderately (by up to a factor of two) toward the MC periphery.…”
Section: Introductionmentioning
confidence: 99%